Clinical Progress of Targeted Therapy for Breast Cancer: A Comprehensive Review - Debnath, Abhijit; Mazumder, Rupa (Current Cancer Drug Targets, 2025)
The discovery of effective breast cancer therapy is both urgent and daunting, beset by a myriad of challenges that range from the disease's inherent heterogeneity to its complex molecular underpinnings. Drug resistance, the intricacies of the tumor microenvironment, and patient-specific variables further complicate this landscape. The stakes are even higher when dealing with subtypes like triple-negative breast cancer, which eludes targeted hormonal therapies due to its lack of estrogen, progesterone, and HER2 receptors. Strategies to overcome such challenges include combinations of drugs and identifying new drug targets. Developing new drugs based on such targets could be a better solution than relying on costly immunotherapy or combinational therapies. In this review, we have endeavored to comprehensively examine the proven therapeutic drug targets associated with breast cancer and elucidate their respective molecular mechanisms and current clinical status. This study aims to facilitate researchers in conducting a comparative analysis of different targets to select single and multi-targeted drug discovery approaches for breast cancer.
Keywords: breast cancer drug targets